2010
DOI: 10.1016/j.amjcard.2010.01.352
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms and the Cardiovascular Risk of Non-Steroidal Anti-Inflammatory Drugs

Abstract: The cardiovascular safety of cyclooxygenase-2 (COX-2) selective non-steroidal anti-inflammatory drugs (NSAIDs) is of concern, although the majority of users remain free of adverse outcomes. A gene-drug interaction may contribute to the variation in individual response to NSAIDs.In a case-only study of 460 patients selected from a cohort admitted for an acute coronary syndrome we genotyped 115 single nucleotide polymorphisms (SNPs). We observed statistically significant gene-drug interactions between NSAID expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 36 publications
(45 reference statements)
0
8
0
6
Order By: Relevance
“…This may be attributed to genetic differences between patients. In fact, two PTGS1 SNPs (rs10303135 and rs12353214) were significantly associated with acute coronary syndrome in patients taking celecoxib as found by St Germaine et al [29]. Kraus et al [20] found two variants of the prostaglandin E2 synthase gene (rs2241271 and rs2302821), one in the C-reactive protein gene (rs1800947) and three in the epidermal growth factor receptor signaling gene (rs6017996, rs6018256, and rs6018257), to be associated with celecoxib cardiovascular side effect.…”
Section: Celecoxib Pharmacodynamicsmentioning
confidence: 85%
“…This may be attributed to genetic differences between patients. In fact, two PTGS1 SNPs (rs10303135 and rs12353214) were significantly associated with acute coronary syndrome in patients taking celecoxib as found by St Germaine et al [29]. Kraus et al [20] found two variants of the prostaglandin E2 synthase gene (rs2241271 and rs2302821), one in the C-reactive protein gene (rs1800947) and three in the epidermal growth factor receptor signaling gene (rs6017996, rs6018256, and rs6018257), to be associated with celecoxib cardiovascular side effect.…”
Section: Celecoxib Pharmacodynamicsmentioning
confidence: 85%
“…In a large nested case cohort study in Denmark, Vogel and colleagues found no interaction between two polymorphisms of the COX‐2 gene: rs5275 (studied here) and rs689466, and recent consumption of NSAIDs [41]. In a case only study of subjects with ACS, St Germaine and colleagues in Quebec, Canada studied a total of 14 polymorphisms of the COX‐2 gene and found no interaction with use of NSAIDs [42]. Significantly, St Germaine and colleagues also found no interaction between polymorphisms of CYP2C9 and NSAID use.…”
Section: Discussionmentioning
confidence: 99%
“…Изучалась роль генетического полиморфизма гена PTGS1 в развитии кардиотоксичности НПВП. В когортном исследовании Recurrence and Inflammation in the Acute Coronary Syndromes Study (n = 1210) было отобрано 115 пациентов с острым коронарным синдромом (ОКС), принимавших НПВП (рофекоксиб, целекоксиб и неселективные НПВП), сравнивали с группой из 345 пациентов, не применявших НПВП [21]. Два одиночных нуклеотидных варианта гена PTGS1 (rs10303135 и rs12353214) были статистически значимо связаны с ОКС преимущественно для селективных ингибиторов ЦОГ-2 -ОР составил 6,94 для rs10303135 и 7,11 для rs12353214 [21].…”
Section: влияние генетического полиморфизма фармакологических мишенейunclassified